Keragaman Fungi Mikoriza Arbuskula Pada Tumbuhan Pokem [Setaria italica (L.) Beauv.] dengan Metode Traping - Suharno Suharno; Rosye H.R. Tanjung; Verena Agustini; Supeni Sufaati (Jurnal Biologi Papua, 2015)
Arbuscular Mycorrhizal Fungi (AMF) plays important role in increasing plant growth and plant protection against pathogen. Its diversity depends on their habitat, including the abundance and distribution of the host plant on agricultural area. This research has aim to explore the diversity of AMF from the rhizosphere of Pokem (Setaria italica) using trapping methods. Soil samples were collected from Numfor Island, Biak Numfor, Papua. The isolation of AMF from the soil sample was elucidated by wet sieving method. Every different spore then was inoculated to the root of Desmodium heterocarpon to propagate and monosporic culture was grown on Shorgum bicolor.  The result showed that the number of the spore that was obtained by traping method increased up to 63,63%. Single spores inoculation of AMF on D. heterocarpon was high percentage (85%) of success. On average, Monosporic culture of single spore inoculation on S. bicolor reached up to 30,53 spores/10g soil sample.  There are 6 genera (9 species) were obtain in this study, namely Glomus, Claroideoglomus, Scutellospora, Gigaspora, Ambispora and Acaulospora. Furthermore, identification using molecular method should be done for proper identification.Key words: AMF, plant rhizosfer, S. italica, trapping methods